A Comparative Study of International and Asian Criteria for Overweight or Obesity at Workplaces in Singapore. (May 2021) - Nazeha, Nuraini; Sathish, Thirunavukkarasu; Soljak, Michael; Dunleavy, Gerard; Visvalingam, Nanthini; Divakar, Ushashree; Bajpai, Ram Chandra; Soh, Chee Kiong; Christopoulos, George; Car, Josip
To compare the prevalence of and risk factors associated with overweight or obesity between the international (body mass index [BMI] ≥25 kg/m 2 ) and Asian (BMI ≥23 kg/m 2 ) criteria in a working population in Singapore. This was a cross-sectional analysis of a cohort study of 464 employees (aged ≥21 years) conducted at 4 workplaces in Singapore. The prevalence of overweight or obesity was 47.4% and 67.0% with the international and Asian criteria, respectively. With both the criteria, higher age, male sex, Malay ethnicity (vs Chinese), lower white rice intake, and consumption of sugar-sweetened beverages were positively associated with overweight or obesity. Participants with poorer mental health and higher levels of thermal comfort in the workplace were positively associated with overweight or obesity only with the Asian criteria. The use of international criteria alone in this population could have overlooked these risk factors that are highly relevant to the Singapore context.